Spontaneous endometriosis associated with an umbilical hernia: A case report and review of the literature. (2017) - Ismael, Hishaam; Ragoza, Yury; Harden, Angela; Cox, Steven
Highlights: Primary umbilical endometriosis is rare and the presence of an underlying hernia makes it a diagnostic challenge. Only 7 cases have been reported in the literature. Our patient underwent an en-bloc resection of the hernia sac, endometrioma and umbilicus with reconstruction. There is no disease recurrence at 6 months. MRI is the preoperative imaging modality of choice and there is a limited role for preoperative FNA and medical management. Abstract: Introduction: Umbilical endometriosis occurring in the presence of an underlying hernia is extremely rare and presents a diagnostic challenge for the general surgeon. We present an interesting case and perform a comprehensive review of the literature. Methods: Medline and PubMed were queried for all cases of spontaneous umbilical endometriosis associated with an umbilical hernia. Data was analyzed and is presented along with an interesting case. Results: Only 7 cases have been reported in the literature. Median age was 38 years. Time to presentation was long (up to 5 years) and the majority had cyclical symptoms related to menstruation. All patients, including our case, were treated surgically. Discussion: Spontaneous umbilical endometriosis with an underlying hernia is often missed preoperatively. Preoperative suspicion warrants axial imaging for better operative planning and patient counseling. Surgery consists of enbloc excision of the umbilicus, implant and the hernia sac to avoid residual disease and reduce recurrence. The hernia defect can be repaired primarily or using mesh and the umbilicus reconstructed using skin flaps if necessary. Conclusions: Surgery is the mainstay of therapy for umbilical endometriosis associated with an underlying hernia. Clinical suspicion warrants preoperative imaging, and follow-up with a gynecologist is essential to address any pelvic disease.